Juvenile distal spinal muscular atrophy of upper extremities in Chinese males: a single fibre electromyographic study of arms and legs. Issue 2 (February 1991) - Chan, Y W; Kay, R; Schwartz, M S
Abstract : Single fibre electromyography (SFEMG) was performed on six young Chinese males with distal spinal muscular atrophy of the upper extremities. Abnormal SFEMG findings of increased fibre density, jitter and blocking were recorded over both arms and legs in all patients, suggesting a more generalised disturbance than would appear clinically.